Investigation on the potential of orange peel waste in the production of useful homemade solution - Azian, Othman (2013)

(untitled)
Homemade solution from fermented orange peel has a high potential to be used as multipurpose cleaning agent. It was produced by undergoing fermentation process using a mixture of brown sugar, orange peel waste and water with correct proportion for at least 3 months. This proposed study was investigating the usefulness of the fermentation broth from orange peel waste as a dish cleaning detergent. In addition, it also aims to fractionate the protein mixture from different age of fermentation and identify its possible content. A proposed method for this study is the comparison of the cleaning power of the fermentation broth from different age with solvent. While, the possible content was examined by determining the distribution of molecular weight by using size exclusion chromatography (SEC), determination the molecular weight of protein in the sample by using Sodium Dodecyl Sulfate Poly Acrylamide Gel Electrophoresis (SDS-PAGE) and by using High Performance Liquid Chromatography (HPLC) to detect possible organic acids. The results showed that 3 months fermentation broth has the highest cleaning power followed by 5 months and 1 month fermentation broths. While based on SEC result, it showed that all ages fermentation broths may contain α-amylase, protease and lipase and SDS-PAGE result proved that the existence of these three enzymes in the fermentation broths. Lastly, HPLC results showed that all ages fermentation broths contain lactic acid and succinic acid. In conclusion,3 months fermented broth from orange peel waste has the highest cleaning power and is quite comparable to the dish cleaning detergent. Other than that, all ages fermentation broths were fractionate to different kind of proteins and the possible contents were identified.